Equality, Rawls and realism: Has the public debate caught up with the policy theory, or left it behind?. Issue 4 (March 2015) - Jackson, Ben
<x xml:space="preserve">Abstract</x> Works of 'popular politics' and academic research alike have pushed issues of equality into the political spotlight. But, Ben Jackson warns, the theoretical debate may be becoming more inegalitarian in its outlook just as British political culture moves in the opposite direction.